Factores asociados a enfermedad trofoblástica gestacional en el Hospital Hipólito Unánue durante el período de enero del 2014 a diciembre del 2018 - Huanca-Llamo, Johana (2019)
Objective: To determine the risk factors associated with gestational trophoblastic disease in patients treated in an outpatient office of the Gynecobstetrics service of the National Hospital Hipólito Unanue between January 2014 and December 2018. Methods: An observational, retrospective, analytical study of cases and controls was conducted. A total of 60 cases were taken as a sample and 120 stories were reviewed as a control group. The information obtained from the review of medical records was recorded in the data collection form. The odds ratio was determined with their respective confidence intervals (CI = 95%). For the multivariate analysis, a binary logistic regression model was used. Results: In the bivariate analysis, the factors associated with gestational trophoblastic disease were the history of abortion (OR 6.54; 95% CI 3.12 - 13.74; p <0.001) and multiparity (OR 3.35; 95% CI: 1.47 - 7.65; p <0.001). Age under 20 years was associated with a lower frequency (OR: 0.13; CI: 0.03-0.48 p <0.001). In the multivariate analysis, the only variables that showed significance were the history of abortion (OR 4.85; 95% CI 1.82-12.91; p = 0.002) as a risk factor and age under 20 years as a protective factor (OR 0.08; 95% CI 0.02 -0.32; p <0.001). Conclusion: The history of abortion and multiparity were associated with the presence of gestational trophoblastic disease, while the age under 20 years behaved as a protective factor.